RESPONSIVITAS DINAS PENGENDALIAN PENDUDUK, KELUARGA BERENCANA, PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN SUMEDANG MELALUI KEGIATAN REMBUK STUNTING DALAM UPAYA PENURUNAN ANGKA STUNTING DI KABUPATEN SUMEDANG - Nureza, Dea Siti (LPPM UNSAP & FISIP UNSAP, 2025)
This study aims to determine the responsiveness of the Population Control, Family Planning, Women's Empowerment, and Child Protection Agency of Sumedang Regency in efforts to reduce stunting rates through stunting discussion activities. The method used in this study is qualitative. This study also highlights the importance of inter-agency coordination and effective monitoring to ensure the success of the stunting reduction program in Sumedang District. The results of the study show that despite significant efforts by the local government, there are still challenges in program implementation that need to be addressed to achieve the expected stunting reduction targets. The recommendations provided by the authors include enhancing the skills of DPPKBP3A staff in Sumedang District, particularly in family accompaniment and child growth monitoring, increasing the availability of adequate and qualified human resources, and improving collaboration among other sectors to ensure more targeted program implementation.